Menanamkan literasi keuangan dan investasi pada remaja melalui game-based learning: Rally Games - Harijanto, Jessica Lorita; Saputra, Louis Nichollas; Ezar, Grecia Jeslyn; Linawati, Nanik (Nur Science Institute, 2024)
Understanding the concept of personal financial management is crucial for today's teenagers, as the skill for financial decision-making. Therefore, teenagers must be equipped with financial planning knowledge as early as possible. One form of financial knowledge provision to teenagers has been carried out by Petra Christian University Finance and Investment students through community service at Frateran Catholic High School, Surabaya. The purpose is to make teenagers aware of the importance of personal financial management and develop skills in making wise financial decisions. The method used in the activity was interactive delivery of material through discussions and supported by rally games activities. This activity was designed to attract teenagers at Frateran Catholic High School to understand more about financial literacy. The rally games method covered supply-demand, interest rates, and investment instruments allocated in three different stations. The results showed an increase in the teenagers' understanding of the concept of financial literacy. The teenagers were able to identify investment instruments and realized the importance of financial management. Thus, this activity succeeded in having a positive impact on improving teenagers' financial literacy.